From Mao Zedong to Xi Jinping: China towards a New Era - Tian, Robert Guang; Yangkuo, Li (Advances in Social Sciences Research Journal, 2021)
China is a large socialist developing country, and the CPC is the core force chosen by the Chinese people to lead it. Mao Zedong was the creator of the Communist Party of China and the People's Republic of China. He led the Chinese people to complete the cause of liberation, carried out socialist construction and began to march toward modernization, forming the great Mao Zedong Thought. Xi Jinping inherited Mao Zedong Thought. He put forward the strategic vision of realizing the Chinese Dream, the great rejuvenation of the Chinese nation. In the new international environment and under the new historical conditions, Xi Jinping has formed a series of highly relevant and continuous theoretical thoughts. His theoretical thoughts have become the guiding ideology for China to become prosperous and strong and make greater global contributions. This paper Outlines the historical process of China from Mao Zedong to Xi Jinping and discusses Xi Jinping's main theoretical ideas.